Cerebrospinal Fluid Cutaneous Fistula after Uneventful Epidural Analgesia - Sze-Ying Thong; Sin Yee Goh (Global Journal of Anesthesiology - Peertechz Publications, 2015)
Cerebrospinous fluid (CSF)-cutaneous fistula is a rare complication of neuraxial blockade. We present a case of a healthy patient who developed cerebrospinal fluidcutaneous fistula after an uneventful epidural catheter insertion for perioperative analgesia. The patient was managed conservatively and the fistula resolved without further issues. The literature is reviewed for similar reports and diagnosis and anagement of this rare complication are discussed.